EFFECTIVE TAX MANAGEMENT STRATEGIES FOR SMALL AND MEDIUM ENTERPRISES (SMEs) - Tampubolon, Amy Septrina; Suryadi, Ibnu; Priyatna, Hilda Nanda; Ersanti, Ersanti (MSJ : Majority Science Journal, 2025)
Tax management remains a pressing challenge for small and medium-sized enterprises (SMEs) in Indonesia, which contribute significantly to the national economy yet often struggle with tax compliance. This study aims to explore effective tax management strategies by conducting a Systematic Literature Review (SLR) of 42 relevant academic and institutional sources published in the last decade. The method involved thematic coding and narrative synthesis of selected literature to identify recurring issues and proposed solutions. The analysis reveals that strategies such as targeted tax education, digital integration, regulatory clarity, institutional collaboration, and incentive alignment are key drivers of compliance. A novel contribution of this study lies in the integrative model proposed emphasizing coordination among stakeholders and contextual adaptation to the Indonesian SME landscape. The findings offer practical insights for policymakers and tax authorities to design more inclusive and effective tax systems tailored to SMEs.